Phase Transitions and Zeros of the Partition Function: An introduction - dos Anjos, Petrus Henrique Ribeiro (Orbital: The Electronic Journal of Chemistry, 2019)
In this revision, I provide a brief and pedagogical introduction to the relation of phase transitions and the zeros of the statistical mechanical partition function. DOI: http://dx.doi.org/10.17807/orbital.v11i2.1362